ДІАЛОГ ЯК ЗАСІБ РОЗВИТКУ ТВОРЧОЇ ОСОБИСТОСТІ УЧНІВ (Педагогіка вищої та середньої школи, 2007)
The article is dedicated to the problem of forming of creative of pupil's cognitive work in the course of teaching dialogue. It also serves as one of the conditions of the development of school's creative potential.